RETRACTED: Tumor Microenvironment in Oral Cancer Following Neoadjuvant Pembrolizumab: Preliminary Analysis of the Histopathologic Findings - Dobriyan, Alex; Gluck, Iris; Alon, Eran; Barshack, Iris; Yahalom, Ran; Vered, Marilena (Frontiers in Oral Health, 2021)
Background: The tumor microenvironment (TME) of oral squamous cell carcinoma (OSCC) is associated with immune suppression, one of the pathways being the programmed death receptor 1 (PD-1) and its ligands (PD-L1/PD-L2). Checkpoint inhibitors of PD-1/PD-L1, like pembrolizumab, have been recently approved for treatment of OSCC. We described the histologic findings in OSCC following neoadjuvant pembrolizumab, including identification of immune-related cell populations and cancer-associated fibroblasts (CAFs). Materials and methods: Patients with OSCC clinical stages 3 and 4 and a combined PD-L1 score >1 were randomized either to the standard oncologic protocol or to the pembrolizumab arm of MK-3475-689 study for Head and Neck, Lip and Oral Cavity. The latter were given two standard doses of 200 mg of pembrolizumab, 3 weeks apart, and then underwent surgical oncologic procedure according to the initial stage. Sections from the resection specimens were analyzed for pathological response to pembrolizumab. Various populations of immune-related cells within the tumor microenvironment were characterized by immunohistochemistry, as were the CAFs. Results: Three patients who were randomized to the pembrolizumab study were described. One patient presented with a tongue SCC, the other two had SCC of the mandibular ridge with bony involvement. Only the patient with tongue SCC showed clinical complete response. Microscopically, the tumor was replaced by a granulomatous type of inflammation. Immunohistochemical stains revealed massive T cell rich (CD3+) infiltrate, with approximately equal amounts of CD4+ and CD8+ cells, numerous macrophages of CD68+ and CD163+ phenotypes; no CAFs were identified. The other two patients were regarded as non-responders as at least 50% of the tumor was viable. The tumor microenvironment of these tumors was generally associated with a lesser extent of inflammatory response compared to the tongue tumor, a variable CD4+/CD8+ ratio and presence of CAFs. Neither T regulatory cells (FOXP3+) nor natural killer cells (CD56+, CD57+) were identified in any of the cases. Conclusion: We showed that characterizing the specific populations of immune-related cells and CAFs after treatment with pembrolizumab, may add to our understanding of the tumor-TME interactions in this setting. These findings should be investigated in future studies on a larger number of patients.